MiR-223-3p and miR-122-5p as circulating biomarkers for plaque instability. Issue 1 (2nd June 2020) - Singh, Sandeep; de Ronde, Maurice W J; Kok, Maayke G M; Beijk, Marcel AM; De Winter, Robbert J; van der Wal, Allard C; Sondermeijer, Brigitte M; Meijers, Joost C M; Creemers, Esther E; Pinto-Sietsma, Sara-Joan
Abstract : Background: In this study, we discovered and validated candidate microRNA (miRNA) biomarkers for coronary artery disease (CAD). Method: Candidate tissue-derived miRNAs from atherosclerotic plaque material in patients with stable coronary artery disease (SCAD) (n=14) and unstable coronary artery disease (UCAD) (n=25) were discovered by qPCR-based arrays. We validated differentially expressed miRNAs, along with seven promising CAD-associated miRNAs from the literature, in the serum of two large cohorts (n=395 and n=1000) of patients with SCAD and UCAD and subclinical atherosclerosis (SubA) and controls, respectively. Result: From plaque materials (discovery phase), miR-125b-5p and miR-193b-3p were most upregulated in SCAD, whereas miR-223-3p and miR-142-3p were most upregulated in patients with UCAD. Subsequent validation in serum from patients with UCAD, SCAD, SubA and controls demonstrated significant upregulation of miR-223-3p, miR-133a-3p, miR-146-3p and miR-155-5p. The ischaemia-related miR-499-5p was also highly upregulated in patients with UCAD compared with the other groups (SCAD OR 20.63 (95% CI 11.16 to 38.15), SubA OR 96.10 (95% CI 40.13 to 230.14) and controls OR 15.73 (95% CI 7.80 to 31.72)). However, no significant difference in miR-499-5p expression was observed across SCAD, SubA and controls. MiR-122-5p was the only miRNA to be significantly upregulated in the serum of both patients with UCAD and SCAD. Conclusion: In conclusion, miR-122-5p and miR-223-3p might be markers of plaque instability.